Answer:
Step-by-step explanation:
- Pythagorean theorem
Answer:
-6
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
x+14=7x+32−3x
x+14=7x+32+−3x
x+14=(7x+−3x)+(32)(Combine Like Terms)
x+14=4x+32
x+14=4x+32
Step 2: Subtract 4x from both sides.
x+14−4x=4x+32−4x
−3x+14=32
Step 3: Subtract 14 from both sides.
−3x+14−14=32−14
−3x=18
Step 4: Divide both sides by -3.
−3x/−3=18/−3
x=−6
Answer:
A
Step-by-step explanation:
2x2.5x3= 15
2x2.5x4.5=22.5
2.5x3x4=30
2.5x2x4=20
To much of an open ended question
Why don’t you round the last answer